Soluble MD-2 and Heme in Sickle Cell Disease Plasma Promote Pro-Inflammatory Signaling in Endothelial Cells - Zhang, Ping; Nguyen, Julia; Abdulla, Fuad; Nelson, Alexander T.; Beckman, Joan D.; Vercellotti, Gregory M.; Belcher, John D. (Frontiers in Immunology, 2021)
Recent evidence indicates that hemolysis in sickle cell disease (SCD) promotes inflammation via innate immune signaling through toll-like receptor 4 (TLR4). Free heme released by hemolyzed red blood cells can bind to myeloid differentiation factor-2 (MD-2) and activate TLR4 pro-inflammatory signaling on endothelium to promote vaso-occlusion and acute chest syndrome in murine models of SCD. MD-2 is co-expressed with TLR4 on cell membranes, but in inflammatory conditions, soluble MD-2 (sMD-2) is elevated in plasma. sMD-2 levels were significantly increased in human and murine sickle (SS) plasma as compared to normal (AA) plasma. Human umbilical vein endothelial cells (HUVEC) and human lung microvascular endothelial cells incubated with human SS plasma had significant increases in pro-inflammatory IL-8, IL-6, and soluble VCAM-1 secretion compared to endothelial cells incubated with AA plasma. The increase in HUVEC IL-8 secretion was blocked by depletion of sMD-2 from SS plasma and enhanced by the addition of sMD-2 to AA plasma. The TLR4 signaling inhibitor, TAK-242, inhibited HUVEC IL-8 secretion in response to SS plasma by 85%. Heme-agarose pull-down assays and UV/Vis spectroscopy demonstrated that heme binds to sMD-2. Hemopexin, a high affinity heme-binding protein, inhibited HUVEC IL-8 secretion induced by SS plasma or SS and AA plasma supplemented with sMD-2. These data suggest that sMD-2 bound to heme might play an important role in pro-inflammatory signaling by endothelium in SCD.